Employees’ peak experience at work: Understanding the triggers and impacts - Fu, Xiehong; Ma, Jingru (Frontiers in Psychology, 2022)
The importance of providing a positive employee experience (EX) has gotten a lot of attention in recent years. However, peak experience (PE), as a highly positive experience, has been studied and applied in the field of human resource management only to a very limited extent. We still know little about how employees’ peak experience (EPE) happens and what the impact will be. Therefore, based on the affective events theory and the two-factor theory, our research conducted an in-depth exploration of EPE through three studies. In Study 1, we constructed a theoretical model centered on EPE based on and interview data. In Study 2, we developed and validated a scale for measuring triggers of EPE, which is a four-dimensional scale (elevation, insight, pride, and connection) with 16 items. In Study 3, we adopted structural equation modeling (SEM) to examine the relationship between EPE and its triggers as well as its impacts using data from 424 valid questionnaires. Our research shows that elevation, insight, pride, and connection can trigger EPE; employees are more likely to have proactive behavior (PB) and word-of-mouth referrals after they have PE; and the more job-relevant the triggers are, the stronger the association between PE and PB is. Our research provides a reliable and effective measurement tool for scholars to study EPE, broadens the findings of PE and EX, and points out feasible measures for organizations to create EPE.